Calculation of core‐level electron spectra of ionic liquids. Issue 14 (6th May 2020) - Lembinen, Meeri; Nõmmiste, Ergo; Ers, Heigo; Docampo‐Álvarez, Borja; Kruusma, Jaanus; Lust, Enn; Ivaništšev, Vladislav B.
Abstract: On the example of 40 ion pairs (5 cations times 8 anions), this study demonstrates how the core‐level binding energy values can be calculated and used to plot theoretical spectra at low computational cost using density functional theory methods. Three approaches for obtaining the binding energy values are based on delta Kohn–Sham (ΔKS) calculations, 1s KS orbital energies, and atomic charges. The ΔKS results show reasonable agreement with the available experimental X‐ray photoelectron data. The 1s KS orbital energies correlate well with the ΔKS results. Atomic charge correlation with ΔKS is improved by accounting for the charges of neighboring atoms. Assignment of binding energies to atoms and the applicability of the mentioned methods to model systems of ionic liquids are discussed. Abstract : This study shows how the core‐level binding energy values can be calculated and used to plot theoretical spectra using three density functional theory‐based approaches: delta Kohn–Sham (ΔKS) calculations, 1s KS orbital energies, and atomic charges. Good agreement with the experimental X‐ray photoelectron data is established for the ΔKS results.